Analysis Of Student Mistakes In Solving Mathematics Problems On The Topic Of Operations In Algebraic Forms For Class VIII SMP Negeri 4 Kawangkoan - Jainab Devira Kumontoy; Victor R. Sulangi; Vivian E. Regar (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
When learning mathematics, students sometimes experience errors in understanding concepts, data, procedures, and principles, especially in algebraic operations. This research analyzes students' errors in solving mathematics problems on algebraic operations material. The research method used is a descriptive method with a qualitative approach. The research subjects were class VIII students at SMP Negeri 4 Kawangkoan. The instruments used were written tests, interviews, and expert validation. Data analysis techniques use qualitative techniques, including data collection, reduction, and conclusion. The conclusions obtained include that students experience three types of errors in solving mathematics problems: data errors, theorem or definition errors, and technical errors.